Enhancing elementary school teachers’ competence in recognizing and supporting gifted students with learning disabilities in Saudi Arabia - Alsamiri, Yasir A. (Frontiers in Education, 2024)
This research investigates the competence of elementary school teachers in Saudi Arabia in recognizing and supporting gifted students with learning disabilities. Two research questions guided the inquiry: RQ1: How do elementary school teachers in Saudi Arabia perceive the impact of professional development, on increasing awareness about students with giftedness and learning disabilities? RQ2: How do elementary school teachers in Saudi Arabia perceive the academic challenges addressed by the series of workshops that created collaborative groups for the discussion of student needs? Using a qualitative approach, in-depth interviews were conducted with 10 certified elementary teachers in Medina City. The study identified two key themes through thematic analysis. The first theme emphasizes the impact of professional development on increasing teachers' awareness of students with giftedness and learning disabilities. Training provided insights into identifying students with learning disabilities and recognizing those with giftedness, emphasizing the need for ongoing training and collaboration. The second theme emerged from workshops creating collaborative groups for discussing student needs, highlighting the power of recognizing individual differences and collaborative efforts for supporting diverse needs. The findings underscore the importance of ongoing professional development and collaboration in improving the capacity of elementary school teachers in Saudi Arabia. These insights have implications for enhancing teacher training programs and developing inclusive educational policies for twice-exceptional learners.